Single‐Atom to Single‐Atom Grafting of Pt1 onto FeN4 Center: Pt1@FeNC Multifunctional Electrocatalyst with Significantly Enhanced Properties. Issue 1 (4th September 2017) - Zeng, Xiaojun; Shui, Jianglan; Liu, Xiaofang; Liu, Qingtao; Li, Yongcheng; Shang, Jiaxiang; Zheng, Lirong; Yu, Ronghai
Abstract: Nonprecious metal catalysts (NPMCs) FeNC are promising alternatives to noble metal Pt as the oxygen reduction reaction (ORR) catalysts for proton‐exchange‐membrane fuel cells. Herein, a new modulation strategy is reported to the active moiety FeN4 via a precise "single‐atom to single‐atom" grafting of a Pt atom onto the Fe center through a bridging oxygen molecule, creating a new active moiety of Pt1 O2 Fe1 N4 . The modulated FeNC exhibits remarkably improved ORR stabilities in acidic media. Moreover, it shows unexpectedly high catalytic activities toward oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), with overpotentials of 310 mV for OER in alkaline solution and 60 mV for HER in acidic media at a current density of 10 mA cm −2, outperforming the benchmark RuO2 and comparable with Pt/C(20%), respectively. The enhanced multifunctional electrocatalytic properties are associated with the newly constructed active moiety Pt1 O2 Fe1 N4, which protects Fe sites from harmful species. Density functional theory calculations reveal the synergy in the new active moiety, which promotes the proton adsorption and reduction kinetics. In addition, the grafted Pt1 O2  dangling bonds may boost the OER activity. This study paves a new way to improve and extend NPMCs electrocatalytic properties through a precisely single‐atom to single‐atom grafting strategy. Abstract : Grafting Pt single‐atoms onto Fe N4 moieties of Fe N C electrocatalyst results in a new active moiety Pt1 O2 Fe1 N4, which exhibits extended electrocatalytic properties including improved oxygen reduction reaction (ORR) stability in acidic media, unexpectedly high OER and HER activities. The protection of Pt1 O2  to Fe atom, synergy, and dangling bonds in the new active moieties are responsible for the much enhanced multifunctional electrocatalytic properties.